Nutrition in Skin Picking Disorder and Trichotillomania - Grant, Jon E.; Valle, Stephanie; Chamberlain, Samuel R. (Frontiers in Psychiatry, 2021)
Objective: Excessive calorie intake constitutes a global public health concern, due to its associated range of untoward outcomes. Impulsivity and compulsivity have been linked to dietary intake. However, nothing is known about dietary intake and body-focused repetitive behaviors, despite their classification as obsessive-compulsive related conditions, and high co-morbidity with impulsive and compulsive conditions. Methods: 196 adults with trichotillomania or skin picking disorder were recruited. Dietary intake over the preceding year was quantified using the Dietary Fat and Free Sugar Short questionnaire. Relationships between dietary fat/sugar intake and behaviors were evaluated using regression modelling. Results: Sugar intake was significantly related to higher trans-diagnostic compulsivity (p=0.011) and higher non-planning impulsivity (p=0.013) In terms of saturated fat intake, there was no significant relationship to the explanatory variables. A combination high fat/high sugar diet was significantly associated with higher motor impulsivity (p=0.005). Conclusions: Past-year nutrition appears to be significantly associated with trans-diagnostic impulsivity and compulsivity. The role of poor nutrition in these disorders and related conditions, and its link with impulsivity and compulsivity, requires longitudinal research attention; and clinical work should address not only psychiatric symptoms but also impact of lifestyle of overall health.